Application of Nanomaterials in Biomedical Imaging and Cancer Therapy - Chow, James C L (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
To mark the recent advances in nanomaterials and nanotechnology in biomedical imaging and cancer therapy, this book, entitled Application of Nanomaterials in Biomedical Imaging and Cancer Therapy includes a collection of important nanomaterial studies on medical imaging and therapy. The book covers recent works on hyperthermia, external beam radiotherapy, MRI-guided radiotherapy, immunotherapy, photothermal therapy, and photodynamic therapy, as well as medical imaging, including high-contrast and deep-tissue imaging, quantum sensing, super-resolution microscopy, and three-dimensional correlative light and electron microscopy. The significant research results and findings explored in this work are expected to help students, researchers and teachers working in the field of nanomaterials and nanotechnology in biomedical physics, to keep pace with the rapid development and the applications of nanomaterials in precise imaging and targeted therapy.